2021
DOI: 10.20453/reh.v30i4.3883
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of multiple oral pyogenic granuloma, ¿associated with treatment with levothyroxin?

Abstract: El Granuloma piógeno (GP) es una lesión tumoral, no neoplásica, vascular, generalmente solitaria, que se presenta en la cavidad oral o piel, la etiología aún no está muy clara, se considera que es una lesión reactiva a varios estímulos de bajo grado, entre los cuales podemos contar traumas repetidos, agresiones, factores hormonales y ciertos fármacos. El GP múltiple, es un fenómeno raro, generalmente asociado al uso de drogas, como la carbamacepina, ciclosporina, retinoides, levotiroxina, etc. Se presenta el c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…These factors are summarized in Figure 1. Pyogenic granuloma (PG) may manifest after a hypersensitivity reaction associated with the use of drugs such as calcineurin inhibitors (cyclosporine and tacrolimus), carbamazepine, phenytoin, nifedipine, levothyroxine and ramucirumab [20][21][22][23][24][25][26][27]. Additionally, PG is associated with retinoid, antineoplastic and antiretroviral agents [20].…”
Section: Etiopathogenesismentioning
confidence: 99%
See 2 more Smart Citations

Oral Pyogenic Granuloma: A Narrative Review

Lomeli Martinez,
Carrillo Contreras,
Gómez Sandoval
et al. 2023
IJMS
“…These factors are summarized in Figure 1. Pyogenic granuloma (PG) may manifest after a hypersensitivity reaction associated with the use of drugs such as calcineurin inhibitors (cyclosporine and tacrolimus), carbamazepine, phenytoin, nifedipine, levothyroxine and ramucirumab [20][21][22][23][24][25][26][27]. Additionally, PG is associated with retinoid, antineoplastic and antiretroviral agents [20].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Cheney et al described a case series in which they included five pediatric/adolescent patients who developed oral PG after HCT for acute lymphoblastic leukemia, Fanconi anemia, nodular sclerosis Hodgkin's lymphoma, or junctional epidermolysis bullosa [21]. It was suggested that calcineurin inhibitors, which are used for graft versus host disease, play a crucial role due to irritation and chronic inflammatory changes in the oral cavity, leading to tissue Pyogenic granuloma (PG) may manifest after a hypersensitivity reaction associated with the use of drugs such as calcineurin inhibitors (cyclosporine and tacrolimus), carbamazepine, phenytoin, nifedipine, levothyroxine and ramucirumab [20][21][22][23][24][25][26][27]. Additionally, PG is associated with retinoid, antineoplastic and antiretroviral agents [20].…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation

Oral Pyogenic Granuloma: A Narrative Review

Lomeli Martinez,
Carrillo Contreras,
Gómez Sandoval
et al. 2023
IJMS
“…These factors are summarized in Figure 1. Pyogenic granuloma (PG) may manifest after a hypersensitivity reaction associated with the use of drugs such as calcineurin inhibitors (cyclosporine and tacrolimus), carbamazepine, phenytoin, nifedipine, levothyroxine and ramucirumab [21][22][23][24][25][26][27][28][29]. Additionally, PG is associated with retinoid, antineoplastic and antiretroviral agents [21].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Regarding carbamazepine, the release of angiogenic factors stimulated by the inflammatory process and the impairment of liver functions contribute to the development of PG [24]. Levothyroxine has been considered a possible etiological factor in PG through its pro-angiogenic and proliferative effects [25]. Piraccini et al (2010) reported that a side effect in psoriasis or acne patients treated with retinoids (systemic isotretinoin, systemic etretinate, systemic acitretin, topical retinoic acid, and topical tazarotene) is the appearance of periungual PGs.…”
Section: Etiopathogenesismentioning
confidence: 99%

Oral Pyogenic Granuloma: A Literature Review

Lomeli Martinez,
Carrillo Contreras,
Gómez Sandoval
et al. 2023
Preprint